Exercise, music, and the brain: Is there a central pattern generator? - Schneider, S.; Askew, C. D.; Abel, T.; Strüder, H. K. (Journal of Sports Sciences, 2010)
The frequency for movements along the longitudinal axis during running peaks at approximately 3 Hz. Other physiological systems (e.g. heart rate and brain cortical activity) are known to show a dominant frequency of ~3 Hz connected to exercise. As recent studies have proposed a clear correlation between musical tempo, mood, and performance output, we wished to ascertain whether peak locomotion frequency of ~3 Hz during running is synchronized with different intrinsic and extrinsic frequencies. Eighteen healthy regular runners performed three outdoor running sessions at different intensities. Oscillations along the longitudinal axis were recorded using an accelerometer (ActiBelt®). Electrocortical activity was recorded using electroencephalography before and after exercise and analysed in the delta frequency range (2-4 Hz). In addition, the frequency spectra of the participants' favourite musical pieces were analysed. Data revealed a peak frequency at around 2.7 to 2.8 Hz for the vertical acceleration during running. Similar oscillation patterns were found for heart rate and musical pieces. Electroencephalographic delta activity increased after running. Results of this study give reason to speculate that a strong relationship exists between intrinsic and extrinsic oscillation patterns during exercise. A frequency of approximately 3 Hz seems to be dominant in different physiological systems and seems to be rated as pleasurable when choosing the appropriate music for exercising. This is in line with previous research showing that an adequate choice of music during exercise enhances performance output and mood.